THE INFLUENCE OF THE VOLUME AND INTENSITY OF TRAINING LOADS ON THE INDICATORS OF BODY WEIGHT LOSS IN ATHLETES IN TAEKWONDO WTF (Physical Culture and Sport: Scientific Perspective, 2025)
The article investigates the influence of the volume and intensity of training loads on body weight loss indicators in taekwondo athletes aged 18–21. The aim of the study is to determine the influence of the volume and intensity of training loads on the amount of body weight loss in taekwondo athletes who use the Pacer fitness application for smartphones. The study was conducted by the public organization “Taekwondo Federation (WTF) of Ukraine”. It was attended by 36 elite athletes of Ukraine, specializing in taekwondo WTF, aged 18–21. During a month of training using the Pacer mobile application, athletes demonstrated an average body weight loss of 1.31±0.09 kg per session. The average volume of their training loads was 5825.44±455.61 EC, and the duration was 128.75±2.41 min. The study found strong correlations between the decrease in body weight of athletes from the volume of training loads r=0.92, at p
Keywords: taekwondo WTF; body weight; weight loss; volume; intensity; load